1994
DOI: 10.1029/94jb00506
|View full text |Cite
|
Sign up to set email alerts
|

Shear wave velocity and attenuation from pulse‐echo studies of Berea sandstone

Abstract: The pulse‐echo spectral‐ratio technique has been adapted to the determination of ultrasonic shear wave attenuation in sandstone at variable states of saturation and pressure. The method can measure shear attenuation coefficients in the range 0.5 dB/cm to 8 dB/cm to within ±0.5 dB/cm. For the Berea sandstone, this range corresponds to values of the shear quality factor (Qs) between 10 and 100. Spectra of Qs show that between 600 and 1100 kHz, Qs decreases with frequency, particularly at high pressures (up to 70… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 45 publications
(55 reference statements)
0
8
0
Order By: Relevance
“…This model was reduced to Gassmann's theory under zero dead volume condition. Furthermore, various ultrasonic results have shown that shear modulus does not always remain constant after fluid saturation as predicted by Gassmann's theory (Baechle et al, 2009;Green & Wang, 1994;Vialle & Vanorio, 2011). The variation of shear modulus for a fluid-saturated rock, either a net increase (strengthening) or a net decrease (weakening), has been attributed to the combined effect of several factors, such as fluid-solid interaction, clay degradation or expansion, and viscous coupling (Cadoret, 1993;Diethart-Jauk & Gegenhuber, 2018;Khazanehdari & Sothcott, 2003;Tutuncu & Sharma, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…This model was reduced to Gassmann's theory under zero dead volume condition. Furthermore, various ultrasonic results have shown that shear modulus does not always remain constant after fluid saturation as predicted by Gassmann's theory (Baechle et al, 2009;Green & Wang, 1994;Vialle & Vanorio, 2011). The variation of shear modulus for a fluid-saturated rock, either a net increase (strengthening) or a net decrease (weakening), has been attributed to the combined effect of several factors, such as fluid-solid interaction, clay degradation or expansion, and viscous coupling (Cadoret, 1993;Diethart-Jauk & Gegenhuber, 2018;Khazanehdari & Sothcott, 2003;Tutuncu & Sharma, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Four consecutive cycles of hydrate formation and dissociation allowed us to form uniform hydrate distributions (Choi et al., 2014; Spangenberg et al., 2015). The differential pressure (confining minus pore pressure) affects elastic wave properties (e.g., Green & Wang, 1994; Prasad & Manghnani, 1997). So, when pore pressure changed during hydrate formation or dissociation, we changed the confining pressure accordingly to maintain a constant differential pressure in each cycle.…”
Section: Laboratory Experimentsmentioning
confidence: 99%
“…French et al (2016) give 10 −14 and 10 −13 m 2 for the permeabilities of the two sandstones. The diffusivity is given by c = kγ / νS where k is the permeability, γ is the weight density of water (9.81 × 10 4 Pa), ν is the dynamic viscosity of water (10 −3 Pa s), and S is a storage coefficient, equal to 1.5 × 10 −6 m −1 (Green & Wang, 1994). These values give c=0.065 m 2 /s for Berea.…”
Section: Parameter Valuesmentioning
confidence: 99%
“…This gives P0=0.2. Using vs=2.5×103 m/s (Green & Wang, 1994) and G=104 MPa gives trueη^108. Pore pressure rates vary from 0.3 to 1.0 MPa/min.…”
Section: Parameter Valuesmentioning
confidence: 99%